Status of the Fishermen Living at the Tangon River Bank- A Case Study from the North-west of Bangladesh - Fatema, K; Nur, M (Journal of Environmental Science and Natural Resources, 2022)
This study intended to provide information on the fishermen engaged in fishing in the Tangon River, Thakurgaon. To assess their existing status, some essential socio-economic information e.g. literacy, religion, health hazards, sanitation and medical facilities, family structure, income level, types of fishermen, fishing, and constraints were taken into account. Results indicated that the majority of the fishermen (77%) belonged to the age class >35-50 years and were dominated by Muslims (89%). Three educational categories were recorded where illiteracy was main (52%), 24% had a primary level of education, and 24% could only sign. This survey revealed that the fishermen near Tangon River are leading measurable life due to great financial hardship. Therefore, proper conservation and management measures must be taken to enhance the fisheries biodiversity in the river so that the fishermen can harvest sufficient fish on a sustainable basis. The government, as well as non-government organizations (NGOs), should take appropriate initiatives to enhance their living standard and to improve such techniques/alternatives that can benefit the underprivileged fishermen to hold present fishing profession in the Tangon River. Environ. Sci. & Natural Resources, 13(1&2): 70-75, 2020